2021
DOI: 10.33988/auvfd.680747
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary supplementation of natural antioxidants and coated calcium butyrate on carcass traits, serum biochemical parameters, lipid peroxidation in meat and intestinal histomorphology in broilers

Abstract: The aim of this study was to investigate the effects of vitamin E, grape seed extract and green tea extract with or without supplementation of coated calcium butyrate in broilers based on carcass traits, some biochemical parameters, intestinal morphology and lipid peroxidation in meat. Two hundred fifty-two one-day-old broiler chicks were divided into nine groups, one control and eight experimental. Control group fed only a basal diet (control). The experimental groups' diets contained feed additives as; coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…The higher concentrations of Fe and Cu in the muscles, Cu in the proventriculus, and Fe in the heart in the CAM.IR, FLA.IR, and SUN.IR treatment groups may be associated with the high blood levels of these elements, to some extent reflecting their concentrations in the entire organism. The levels of iron and copper in an organism largely depend on the diet and the degree of gastrointestinal absorption [45]. Equally interesting is the higher level of Ca in the breast muscles and liver of the CAM.IR and FLA.IR broiler chickens as compared with the control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher concentrations of Fe and Cu in the muscles, Cu in the proventriculus, and Fe in the heart in the CAM.IR, FLA.IR, and SUN.IR treatment groups may be associated with the high blood levels of these elements, to some extent reflecting their concentrations in the entire organism. The levels of iron and copper in an organism largely depend on the diet and the degree of gastrointestinal absorption [45]. Equally interesting is the higher level of Ca in the breast muscles and liver of the CAM.IR and FLA.IR broiler chickens as compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Equally interesting is the higher level of Ca in the breast muscles and liver of the CAM.IR and FLA.IR broiler chickens as compared with the control. As demonstrated by investigations of broiler chickens conducted by Gümüş et al [45], an adequate level of Ca in the diet inhibits the intensity of lipid peroxidation in meat with maintenance of adequate dietary nutrient proportions in meat. The authors proposed that the combination of Ca sources with natural antioxidants in the diet could be used to improve carcass characteristics and antioxidant capacity in broiler meat.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that dietary supplementation with sodium butyrate could enhance intestinal morphology and performance in broilers ( Kaczmarek et al., 2016 ), as well as improve the yolk color and microbial diversity in a dose-dependent manner in laying hens ( Zhang et al., 2022c ). Similarly, Ca butyrate, functioning as butyric acid in the acidic environment of the proximal digestive tract of birds, was also noted to improve the growth performance, intestinal health, and carcass traits in broilers ( Gümüş et al., 2021 ; Ocejo et al., 2017 ). Further to this, it also increased body weight gain and exhibited anti-inflammatory/antioxidant effects in Japanese quails ( Abd El-Wahab et al., 2019 ), and improved eggshell quality in aged laying hens ( Song et al., 2022 ).…”
Section: Introductionmentioning
confidence: 95%
“…In addition to the beneficial effects on intestine and performance in piglets and broiler chickens (Liu et al, 2022; Piva et al, 2002; Xu et al, 2021), the supplementation with C. butyricum or sodium butyrate was also noticed to improve the reproductive performance, egg quality, and intestinal morphology in hens (Wang et al, 2021). Ca butyrate as another butyric acid supplement was also noticed to promote growth performance, intestinal health, and carcass traits in broilers (Gümüş et al, 2020; Ocejo et al, 2017), increased body weight gain and exhibited an anti‐inflammatory/antioxidant effect in Japanese quails (Abd El‐Wahab et al, 2019), and improved the eggshell quality in aged laying hens (Song et al, 2022). Given the above, apart from the direct addition of C. butyricum to the diet, supplementing the product of Ca butyrate from biomass using C. butyricum (fermented Ca butyrate), which contains Ca, butyrate, and C. butyricum might exert some positive effects in ovarian function and laying performance of post‐peak layer hens.…”
Section: Introductionmentioning
confidence: 99%